ANALISIS PENGARUH PERUBAHAN NILAI HARGA ACUAN BATUBARA TERHADAP KELAYAKAN PENAMBANGAN TAMBANG BAWAH TANAH OMBILIN 1 (SAWAHLUWUNG) PT. BUKIT ASAM – UPO - Yolanda Noverista; Murad Murad; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2015)
PT. Bukit Asam - UPO is an underground coal mining company conducted in the area Ombilin I (Sawahluwung), Ombilin II (Waringin-Sugar) and Ombilin III (Sigalut). Excess coal production compared to the low demand becomes a significant factor for the price of coal fell for the last few years. So far, the Government has issued a monthly coal reference price (HBA and HPB) since January 2009 for use by manufacturers of coal to all the places and contact services. But the official implementation HBA started since September 2011. In addition, the reference price of coal to be used by holders of Production Operation IUP, IUP specialized production operations as well as CCoWs as a reference in determining the selling price of coal for a given period. Therefore, it needs to be calculated budget plans annual production of coal mining PT. Bukit Asam UPO so that it can be seen in corporate profits and the value of the minimum reference price of coal mining in order to still meet the minimum profit required.The method used in this research is quantitative research methods. Where do the initial learning of what will be done and the collection of data necessary for the manufacture of paper so that when the data processing that starts from the calculation of the budget plan, coal reference price comparison with the price of the exchange and analysis of the effects of changes in the reference price of coal. Can be concluded from these data.From research conducted then obtained Budget Plan (RAB) for one year PT. Bukit Asam UPO is Rp. 44.638.890.400.00. Minimum benchmark coal prices obtained in December 2014 at 64,65, it shows the value of the company's profit decreases with the increase in the exchange rate increasingly rises. Minimal HBA preferably above 45.65 with the exchange rate of Rp. 12.000 / $, because if theHBA under 45,65 would suffer losses.